Socio-Psychological Problems of the Protagonist in Kavita Kane’s Karna’s Wife: The Outcast’s Queen. An Analytical Study (2022)
This paper explores the socio-psychological problems of the protagonist in Kavita Kane’s Karna’s Wife: The Outcast’s Queen, discoursing the causes for the socio-psychological problems that the marginalised were subjected to in the epic era. This research aims to study the-then social conditions and analyse how they cause the trauma in the psyche of the protagonist. While the Freudian psychological approach interprets that the causes for the psychological distress are to be searched for in the unconscious minds, the Marxist approach asserts that they are to be seen in the then-material conditions of social life. So, the Marxist literary critical approach is necessary for carrying out this research, tracing the dialectical relationship between the human psyche and the then-contemporary social relations. It is asserted that the social discriminations would adversely cause socio-psychological problems among individuals and it was true in the case of Karna, too.